Business Process Management Model for Customer Satisfaction in an SME in the Gastronomy Sector (LACCEI, 2024)
The purpose of this study is to design a business process management model for customer satisfaction for an SME in the gastronomic sector being the research of a non-experimental and prospective cross-sectional nature, with a mixed approach due to the qualitative and quantitative data. The population is all the processes of the organization, where the sample for convenience are exactly 15, considering one of them as the unit of study, also 150 customers are part of this sample. Concluding that the business process management model designed is appropriate to the reality and conditions of the SME, demonstrating it in processes optimization in order to achieve customer satisfaction, using tools such as information systems and process redesign, which would allow a reduction in time and costs in key processes such as customer service and attention and food preparation, thus optimizing valuable resources for the organization, on the other hand, they proposed new processes such as production planning, input standardization, among others to offer a better quality service to customers thus achieving their satisfaction.